Population genetics analyses of North-East Indian indigenous rice landraces revealed divergent history and alternate origin of aroma in aus group. Issue 5 (16th October 2019) - Chakraborty, Debarati; Ray, Avik
Abstract: The rice-based agriculture of the Indian subcontinent has been interwoven in the rich socio-cultural fabric of the country. Of which, bio-culturally diverse North-Eastern states nurture thousands of landraces with poorly tapped agronomic traits. In the present study, 27 standard microsatellite data from 171 rice landraces from six states were analysed to understand their genetic diversity and population structure. Further, combining with a global dataset, we determined subpopulation identity using both model-based and multivariate analyses to uncover their history. We found moderate to high genetic diversity and high differentiation [standardized G "ST = 0.57]. The AMOVA partitioned overall variance into within population (75%) and among population (25%). The landraces from six states remained at various degrees of differentiation (pairwise F ST = 0.09–0.41). We have detected a preponderance of aus -type in a majority of aromatic landraces. Rests were japonica and admixed with a little representation of indica . The presence of aromatic aus probably implied assimilation into local culture from the primary aus growing region of Bangladesh and India. Likewise, the arrival of japonica may stem from the exchange of goods among neighbouring dynasties via Southern and Southwestern Silk routes. The shared ancestry may reflect a merger of two ancient cultures. Our analyses also uncovered the existence of aus -type short and medium grain aromatic rice predicting an origin of aroma in aus subpopulation. Collectively, it demonstrated the diversity and divergent history of the rice landraces have been shaped by various socio-cultural interactions operative over time and space.